Pengaruh Application Self Efficacy dan Kompleksitas Teknologi terhadap Adopsi Learning Management System oleh Dosen FKIP UNS pada saat Covid 19 - Muhammad Arif Sudarsono; Kristiani Kristiani; Fery Setyowibowo (Journal on Education, 2023)
This study aims to determine (1) the effect of Application Self Efficacy on LMS adoption by FKIP UNS Lecturers, (2). the effect of technological complexity on LMS adoption by UNS FKIP Lecturers, (3) the effect of Perceived Usefulness and Perceived Ease (TAM) on LMS adoption by UNS FKIP Lecturers. This research is a quantitative study with a population of Lecturers of the Faculty of Teaching and Education, Sebelas Maret University (FKIP UNS) with a total population of 445 lecturers and a total sample of 104 lecturers, from 23 study programs at FKIP UNS. The sampling technique used is random sampling technique, data collection uses a questionnaire, the data analysis used is the Structural Equation Model (SEM). The results of this study are: First, there is a positive and significant influence between Perceived Usefulness (PU) on Behavioral Intention (BI). Second, there is a positive and significant influence between Perceived Ease (PEOU) and Behavioral Intention (BI). Third, there is no significant effect between Perceived Ease (PEOU) on Perceived Usefulness (PU). Fourth, there is no significant effect between Application Self Efficacy (ASE) on Perceived Usefulness (PU). Fifth, there is a positive and significant influence between Application Self-Efficacy (ASE) on Perceived Ease (PEOU). Sixth, there is a positive and significant influence between Technological Complexity (TC) and Perceived Ease of Use (PEOU).